2020
DOI: 10.1051/sicotj/2020033
|View full text |Cite
|
Sign up to set email alerts
|

Total knee arthroplasty after distal femoral osteotomy: a systematic review and current concepts

Abstract: Introduction: Distal Femoral Osteotomy (DFO) is a common procedure for correcting lower limb valgus deformity and lateral compartment overload. Low 20-year survivorship rate was reported with a consequent need for total knee arthroplasty (TKA). This study aims to review literature and to analyse the influence of a previous distal femoral osteotomy on outcomes of patients undergoing TKA. Methods: A systematic literature review was performed in PubMed/Medline and Embase in May 2020. Papers were selected based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…It has been reported that previous open knee interventions like high tibial osteotomies are correlated with inferior functional and clinical outcomes in patients undergoing TKA when compared with those of primary TKA without previous procedures [16][17][18]. Moreover, TKA patients with prior anterior cruciate ligament (ACL) reconstruction have also exhibited inferior outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that previous open knee interventions like high tibial osteotomies are correlated with inferior functional and clinical outcomes in patients undergoing TKA when compared with those of primary TKA without previous procedures [16][17][18]. Moreover, TKA patients with prior anterior cruciate ligament (ACL) reconstruction have also exhibited inferior outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Недостатком этого обзора было то, что во всех публикациях анализировалось небольшое количество пациентов. Тем не менее авторы сделали вывод о том, что предыдущая правильно выполненная остеотомия не влияет на клинические исходы первичного эндопротезирования, результаты которого сопоставимы с результатами эндопротезирования без предшествующей остеотомии [51].…”
Section: Discussionunclassified
“…Total knee arthroplasty (TKA) has shown good outcomes and survivorship [1][2][3][4][5]. However, postoperative anterior knee pain (AKP) is a common problem after TKA and affects patient satisfaction [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%